Pengaruh Pemberian Rebusan Kunyit Asam Terhadap Penurunan Skala Nyeri Dismenorea Pada Remaja di SMA Muhammadiyah 25 Pamulang - Gaung Eka Ramadhan; Putri Nabilah Hafizhah (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK, 2023)
Dysmenorrhea is a pain that is felt during menstruation. Primary dysmenorrhea is caused by increased levels of prostaglandins (PGF2?) which are produced by the lining cells of the uterus. This study aims to determine the effect of giving turmeric acid decoction to reduce dysmenorrhea pain scale in adolescents at SMA Muhammadiyah 25 Pamulang. This study used a quasy experimental research design with the one group pretest posttest design method. The population in this study were adolescents in class X and XI SMA Muhammadiyah 25 Pamulang, consisting of 186 people. The number of samples in this study were 18 people using a stratified random sampling technique. The instruments in this study were ½ kg of turmeric, ¼ kg of palm sugar, ½ kg of tamarind, 2000 cc of water, salt, digital scales, blender, measuring cup and filter. The results of statistical tests using the Paired T-test showed a P value of 0.001 (P <0.05), meaning that there was an effect of boiling turmeric acid on reducing the pain scale of dysmenorrhea in adolescents. Based on the results of the study, it is hoped that nurses can provide interventions for treating dysmenorrhea.